2015
DOI: 10.1021/acs.jpclett.5b00780
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Au144(SCH2CH2Ph)60 to Au133(SPh-tBu)52 Nanomolecules: Theoretical and Experimental Study

Abstract: Ultrastable gold nanomolecule Au144(SCH2CH2Ph)60 upon etching with excess tert-butylbenzenethiol undergoes a core-size conversion and compositional change to form an entirely new core of Au133(SPh-tBu)52. This conversion was studied using high-resolution electrospray mass spectrometry which shows that the core size conversion is initiated after 22 ligand exchanges, suggesting a relatively high stability of the Au144(SCH2CH2Ph)38(SPh-tBu)22 intermediate. The Au144 → Au133 core size conversion is surprisingly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 35 publications
3
99
0
Order By: Relevance
“…Thiophenol is a classic example of aromatic thiol. TBBT thiol is found to have similar aromatic ligand effect with minimal variation of the end product except for instance reported case where, Au 133 (SR) 52 (Nimmala et al, 2015 ) is reported with TBBT, but not with thiophenol. This is expected as the surface availability of the nanomolecule decreases as the size increases steric effect by para -tert-butyl groups becomes significant compared to smaller core-size Au 36 (SR) 24 .…”
Section: Ligand Effect Demonstrated By Direct Synthesismentioning
confidence: 73%
See 1 more Smart Citation
“…Thiophenol is a classic example of aromatic thiol. TBBT thiol is found to have similar aromatic ligand effect with minimal variation of the end product except for instance reported case where, Au 133 (SR) 52 (Nimmala et al, 2015 ) is reported with TBBT, but not with thiophenol. This is expected as the surface availability of the nanomolecule decreases as the size increases steric effect by para -tert-butyl groups becomes significant compared to smaller core-size Au 36 (SR) 24 .…”
Section: Ligand Effect Demonstrated By Direct Synthesismentioning
confidence: 73%
“…Thus, ligand effects are not necessarily due to only the ligands' bulkiness but also due to the aromaticity and electronic nature of the ligand structure. Experimentally, we have shown that in the presence of the aromatic TBBT ligand Au 144 (SCH 2 CH 2 Ph) 60 transforms to a new core-size to give Au 133 (SPh- t Bu) 52 (Nimmala et al, 2015 ). We hypothesize the effect of aromatic phenyl rings contribute a favorable inter-ligand interaction while para-tertiary groups create steric repulsion and kinetic effects and trigger the core-size conversion to Au 133 (SPh- t Bu) 52 .…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Formore than two decades, investigations were performed in the absence of precise structural information. It was reported that thiolate-protected Au 144 clusters show promising catalytic activities [24][25][26][27][28] and electrochemiluminescence, [29,30] and can be employed as precursors in the synthesis of Au 99 [31] and Au 133 [12,13,32] nanoclusters.M oreover,A u 144 has applications in organic solar cell [33] and floating memory devices, [34] etc.More importantly, it was also found that thiolate-protected Au 144 exhibits both molecular and bulklike behaviors,w ith its size in the critical transition range.F or example,A u 144 (SR) 60 exhibits ah ighly structured UV-vis-NIR spectrum with absorption bands over the entire region. [35,36] This spectrum indicates the molecular nature of Au 144 ,and was also supported by density functional theory (DFT) calculations.…”
mentioning
confidence: 99%
“…Here it is important to point out that the temperature of fragmentation that could be measured experimentally might significantly differ from the values reported here since all the stabilizations arising from the ligands (such as ligand-ligand interactions and steric effects) have been omitted for practical purposes. Moreover, and despite the large number of observations of core-size conversion of MPC upon ligand exchange under heating [14,[49][50][51], to the best of our knowledge there are not reports on the fragmentation of this type of systems caused solely by the effect of temperature. In addition, modeling the time scales involve in the fragmentation of MPC at room temperature is unfeasible by using ab initio calculations.…”
Section: Resultsmentioning
confidence: 98%